Insulation sheet for battery, manufacturing method thereof, and battery module including the same
Patent Information
- Application Number
- JP2024078446
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-19
- Filing Date
- 2024-05-14
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-05-14
AI Technical Summary
【0024】 一実施形態に係るバッテリー用断熱シートは、優れた断熱性、耐火性、及び難燃性又は不燃性を有し、一つのセルの熱暴走による隣接セルへの熱及び火炎の伝播を抑制することができる。
Smart Images

Figure 2025000551000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat insulating sheet for a battery, a manufacturing method thereof, and a battery module including the same. [Background technology]
[0002] Secondary batteries are power storage systems that provide excellent energy density by converting electrical energy into chemical energy and storing it. Unlike primary batteries, which cannot be recharged, secondary batteries can be recharged, and are widely used in IT devices such as smartphones, cellular phones, laptops, and tablet PCs. In recent years, interest in electric vehicles has increased to prevent environmental pollution, and high-capacity secondary batteries are being adopted for electric vehicles. Such secondary batteries are required to have characteristics such as high density, high output, and stability.
[0003] On the other hand, when a battery contains a large number of high-capacity battery cells such as lithium-ion secondary batteries, it is necessary to thermally insulate adjacent battery cells from each other because one battery cell may overheat and experience thermal runaway for some reason, adversely affecting other adjacent battery cells.
[0004] Therefore, in the past, a plate material or an insulating resin plate was placed between the battery cells to provide insulation and heat between adjacent battery cells.
[0005] The above information disclosed in the Background of the Invention is intended to enhance the understanding of the background of the present invention only, and may therefore include information that does not constitute prior art. Summary of the Invention [Problem to be solved by the invention]
[0006] One embodiment provides an insulating sheet for batteries that has excellent insulating properties as well as fire resistance and flame retardancy or non-combustibility to suppress heat propagation between adjacent cells due to thermal runaway of the battery, a manufacturing method thereof, and a battery module including the same. [Means for solving the problem]
[0007] One embodiment provides a heat insulating sheet for a battery, comprising: an aerogel layer including an aerogel; and a coating layer covering an entire surface of the aerogel layer, the coating layer comprising a flexible polymer and a flame retardant dispersed in the flexible polymer, the coating layer having an elastic modulus of 8 MPa or less as measured by ASTM D882.
[0008] The aerogel has a BET specific surface area of 500 m 2 / g~1,000m 2 / g.
[0009] The aerogel layer may further include a fibrous support and a functional material including a binder, a dispersant, or a combination thereof.
[0010] The fibrous support may be one or more fibers selected from the group consisting of natural fibers, silica fibers, glass fibers, carbon fibers, graphite fibers, mineral fibers, and polymer fibers.
[0011] The binder may include a water-based polymeric binder.
[0012] The dispersant may be one or more selected from the group consisting of a surfactant, a silane coupling agent, and a phosphate salt.
[0013] The aerogel layer may contain 10% by weight to 90% by weight of the aerogel, 5% by weight to 70% by weight of the fibrous support, and 0.5% by weight to 20% by weight of the functional material, based on the total amount of the aerogel layer.
[0014] The flexible polymer may be at least one selected from the group consisting of a fluorine-based polymer, a polyurethane-based polymer, a polyolefin-based polymer, and a silicon-based polymer.
[0015] The flame retardant may be at least one selected from the group consisting of inorganic flame retardants, phosphorus-based flame retardants, nitrogen compound-based flame retardants, silicon-based flame retardants, melamine-based flame retardants, halogen-based flame retardants, and polyhydric alcohol-based flame retardants.
[0016] The flame retardant may consist of a phosphorus-based flame retardant and a polyhydric alcohol-based flame retardant.
[0017] The flame retardant may include a phosphorus-based flame retardant and a polyhydric alcohol-based flame retardant in a weight ratio of 1:0.1 to 1:0.5.
[0018] The content of the flame retardant may be 1% by weight to 25% by weight based on the total amount of the coating layer.
[0019] The coating layer may be free of fillers.
[0020] The thickness of the coating layer may be 20% or less of the total thickness of the battery insulating sheet.
[0021] The flexible polymer may be at least one selected from the group consisting of polyurethane-based polymers and silicone-based polymers, and the flame retardant may be at least one selected from the group consisting of polyhydric alcohol-based flame retardants and phosphorus-based flame retardants.
[0022] Another embodiment provides a method for manufacturing an insulation sheet for a battery, the method including: forming an aerogel layer including an aerogel; and forming a coating layer to cover an entire surface of the aerogel layer, the coating layer including a flexible polymer and a flame retardant dispersed in the flexible polymer.
[0023] Yet another embodiment provides a battery module including a plurality of cells and the insulating sheets disposed between the plurality of cells, respectively. Effect of the Invention
[0024] The insulating sheet for a battery according to one embodiment has excellent insulating properties, fire resistance, and flame retardancy or non-combustibility, and can suppress the spread of heat and flame to adjacent cells due to thermal runaway of one cell.
[0025] In addition, the insulating sheet for a battery according to one embodiment has excellent compression performance, and can ensure mechanical strength and dimensional stability, and can prevent the aerogel layer from falling off due to external impact, making it easy to work with and preventing contamination of the mechanism. [Brief description of the drawings]
[0026] [Figure 1] FIG. 2 is a schematic diagram showing an insulating sheet for a battery according to an embodiment formed between a plurality of cells. [Diagram 2] 1 is a schematic diagram showing a cross-sectional structure of a battery insulating sheet according to one embodiment. [Diagram 3] FIG. 11 is a schematic diagram showing the cross-sectional structure of a heat insulating sheet according to Comparative Example 4. [Figure 4] FIG. 11 is a schematic diagram showing the cross-sectional structure of a heat insulating sheet according to Comparative Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Although the present invention will be described in detail below so as to be easily understood by those skilled in the art, the present invention may be embodied in various different forms and should not be construed as being limited to the embodiments set forth herein.
[0028] Insulation materials are materials that prevent the flow of heat from a high temperature area to a low temperature area, and are used in refrigerators, freezer warehouses, and buildings as well as in various industrial fields including the aircraft, electronic parts, and automotive industries.
[0029] Such a heat insulating material should have excellent heat insulating performance due to low thermal conductivity, and is also required to have sufficient mechanical strength to maintain such heat insulating performance.
[0030] Meanwhile, aerogel is a transparent or translucent cutting-edge material with a nanoporous structure, and has very low density and low thermal conductivity. As such, it not only has great potential as an insulating material, but is also considered a highly efficient super-insulating material that can be used in a variety of industrial fields.
[0031] Furthermore, the greatest advantage of aerogel is that it exhibits lower thermal conductivity than conventional organic insulation materials such as styrofoam, and that it solves the fatal weaknesses of organic insulation materials, namely, vulnerability to fire and the generation of harmful gases during a fire.
[0032] An insulating sheet for a battery according to one embodiment includes an aerogel layer including an aerogel, and a coating layer covering an entire surface of the aerogel layer, the coating layer including a flexible polymer and a flame retardant dispersed in the flexible polymer, and the coating layer may have an elastic modulus of 8 MPa or less as measured by ASTM D882.
[0033] The insulating sheet for a battery having the above structure has excellent heat insulation properties, as well as fire resistance and flame retardancy or non-combustibility, and can suppress the propagation of heat and flame to adjacent cells due to thermal runaway of one cell. In addition, the insulating sheet for a battery has excellent compression performance, can ensure mechanical strength and dimensional stability, can prevent the aerogel layer from falling off due to external impact, and can facilitate work and prevent contamination of the mechanism.
[0034] In one embodiment, the aerogel has a BET specific surface area of 500 m 2 / g~1,000m 2 For example, the aerogel may have a BET specific surface area of 500 m 2 / g~950m 2 / g, 550m 2 / g~950m2 / g, or 600m 2 / g~900m 2 By including an aerogel having a BET specific surface area value within the above range, scattering of the aerogel particles can be prevented and heat insulation can be improved.
[0035] The particle size of the aerogel may be 5 μm to 200 μm, 10 μm to 100 μm, or 20 μm to 60 μm. By including an aerogel having a particle size within the above range, the heat insulating properties can be improved and the heat transfer between the multiple cells can be delayed.
[0036] The content of the aerogel may be 10% by weight to 90% by weight, 30% by weight to 70% by weight, or 40% by weight to 60% by weight based on the total amount of the aerogel layer. By including an aerogel layer containing aerogel within the above range, excellent heat insulating properties of the battery insulating sheet can be obtained.
[0037] In one embodiment, the aerogel layer may further comprise a fibrous support and a functional material comprising a binder, a dispersant, or a combination thereof.
[0038] The fibrous support is contained in the aerogel layer, thereby improving the durability of the battery insulation sheet formed using the same.
[0039] The fibrous support may include fibers used as supports for ordinary heat insulating materials. For example, the fibrous support may be one or more selected from the group consisting of natural fibers, silica fibers, glass fibers, carbon fibers, graphite fibers, mineral fibers, and polymer fibers. As a specific example, the fibrous support may include glass fibers, but is not limited thereto.
[0040] The natural fibers may be, for example, one or more selected from the group consisting of hemp, jute, flax, coir, hemp, and cellulose.
[0041] The mineral fibers may be, for example, mineral fibers comprising one or more selected from the group consisting of basalt, wollastonite, alumina, silica, slag, and rock.
[0042] The polymer fiber may be, for example, one or more selected from the group consisting of nylon, polyimide, polyamide, polybenzimidazole, polybenzoxazole, polyamideimide, polyethyleneterephthalate, polybutyleneterephthalate, polyester, polyethylene (PE), and polypropylene (PP). As a specific example, the polymer fiber may be, but is not limited to, one or more selected from the group consisting of polyimide, polyamide, and polybenzimidazole.
[0043] The fibrous support may be, for example, in the form of wool or chopped strands, but is not limited thereto.
[0044] The average particle size (D50) of the fibrous support may be, for example, 0.1 μm to 20 μm, 0.1 μm to 15 μm, 0.1 μm to 5 μm, 1 μm to 15 μm, or 3 μm to 10 μm. By including a fibrous support having an average particle size within the above range, the structure of the aerogel layer can be made stronger, and the production cost can be reduced.
[0045] The average particle size (D50) can be measured, for example, by a laser diffraction method or a scanning electron microscope (SEM) photograph, and the average particle size (D50) of the particles can be defined as the particle size at 50% of the particle size distribution (the particle size corresponding to 50% of the cumulative volume of the particle size distribution).
[0046] The content of the fibrous support may be 5% by weight to 70% by weight, 25% by weight to 60% by weight, or 30% by weight to 50% by weight based on the total amount of the aerogel layer. When an aerogel layer containing a fibrous support within the above range is formed to produce a battery insulating sheet, durability can be improved.
[0047] The binder may include a water-based polymer binder. For example, the water-based polymer binder may be at least one selected from the group consisting of a water-based polymer, an anionic water-soluble polymer, a cationic water-soluble polymer, and a water-dispersible polymer.
[0048] The aqueous polymer may be, for example, at least one selected from the group consisting of polyvinyl alcohol, polyethylene oxide, polyacrylamide, and polyvinylpyrrolidone, but is not limited thereto.
[0049] The anionic water-soluble polymer may be at least one selected from the group consisting of polymers having functional groups of carboxylic acid, sulfonic acid, sulfate, phosphate, and salts thereof. For example, the anionic water-soluble polymer may be a polymer having a carboxylic acid group, and a specific example thereof may include, but is not limited to, polymaleic acid.
[0050] The cationic water-soluble polymer may be at least one selected from the group consisting of polymers having functional groups of amine, ammonium, phosphonium, sulfonium, and salts thereof. For example, the cationic water-soluble polymer may be a polymer having an amine group, and a specific example may be at least one selected from the group consisting of polyethylene amine and polyamine, but is not limited thereto.
[0051] The water-dispersible polymer may be at least one selected from the group consisting of water-dispersible polyurethane and water-dispersible polyester, but is not limited thereto.
[0052] The binder may include a water-based polymer and a water-dispersible polymer, for example, a water-based polymer having binder properties as well as dispersion properties, and a water-dispersible polyurethane having fire-resistant properties, and a specific example thereof may include polyvinyl alcohol and water-dispersible polyurethane.
[0053] The weight ratio of the aqueous polymer and the water-dispersible polymer may be 1:1 to 1:5, 1:1 to 1:4, or 1:2 to 1:3. When the weight ratio of the aqueous polymer and the water-dispersible polymer is used in combination within the above range, the heat insulation property, dust resistance, and compressibility of the heat insulation sheet can be further improved as well as the fire resistance and mechanical properties.
[0054] The content of the binder may be 0.5% by weight to 20% by weight, 2% by weight to 15% by weight, or 8% by weight to 15% by weight, based on the total amount of the aerogel layer. The battery insulating sheet including the aerogel layer containing the binder within the above range may have improved dust characteristics.
[0055] The dispersant may be at least one selected from the group consisting of a surfactant, a silane coupling agent, and a phosphate salt. Specific examples of the dispersant include, but are not limited to, at least one of a nonionic surfactant, an anionic surfactant, an amphoteric surfactant, a natural surfactant such as lecithin, and a phosphate salt.
[0056] When the dispersant is further included, the dispersion of the aerogel is improved during the preparation of the aerogel layer, and the aerogel can be uniformly dispersed in the fibrous support.
[0057] The content of the dispersant may be 0.1% by weight to 6% by weight, 0.1% by weight to 5% by weight, or 0.1% by weight to 3% by weight, based on the total amount of the aerogel layer. By including the dispersant within the above range, an aerogel layer can be produced at low cost, and an insulating sheet having excellent insulating properties, uniformity, and dust characteristics can be produced using the aerogel layer.
[0058] In one embodiment, the binder and the dispersant may be included in a weight ratio of 1:0.001 to 1:0.67, 1:0.001 to 1:0.5, or 1:0.001 to 1:0.3. When the binder and the dispersant are used in combination in a weight ratio within this range, the aerogel may be more uniformly dispersed in the aerogel layer.
[0059] In one embodiment, the fibrous support may comprise 25% by weight to 60% by weight, the aerogel may comprise 30% by weight to 70% by weight, and the binder may comprise 2% by weight to 15% by weight, based on the total amount of the aerogel layer.
[0060] As a specific example, the aerogel layer may contain 30% to 50% by weight of the fibrous support, 40% to 60% by weight of the aerogel, and 8% to 15% by weight of the binder, relative to the total amount of the aerogel layer. When the aerogel layer is formed within the above ranges, excellent heat insulation can be achieved and durability can be improved, the bonding strength between the fibrous support and the aerogel can be improved, and dust generation can be prevented.
[0061] In one embodiment, the aerogel layer may contain, relative to the total amount of the aerogel layer, 25% by weight to 60% by weight of the fibrous support, 30% by weight to 70% by weight of the aerogel, 2% by weight to 15% by weight of the binder, and 0.1% by weight to 3% by weight of the dispersant.
[0062] As a specific example, the aerogel layer may contain 30% to 50% by weight of the fibrous support, 40% to 60% by weight of the aerogel, 5% to 10% by weight of the binder, and 0.1% to 2% by weight of the dispersant, relative to the total amount of the aerogel layer. When the aerogel layer is formed within the above ranges, excellent heat insulation can be achieved and durability can be improved, the bonding strength between the fibrous support and the aerogel can be improved, and dust generation can be prevented.
[0063] In one embodiment, the flexible polymer contained in the coating layer is not particularly limited as long as it is a polymer having flexibility, and may be, for example, one or more types selected from the group consisting of a fluorine-based polymer, a polyurethane-based polymer, a polyolefin-based polymer, and a silicone-based polymer.
[0064] The fluoropolymer may be, for example, one or more selected from the group consisting of polytetrafluoroethylene (PTFE), perfluoroalkoxyethylene (PFA), fluoroethylenepropylene (FEP), ethylene-tetrafluoroethylene (ETFE), polyvinyldene fluoride (PVDF), and polychlorotrifluoroethylene (PCTFE). The fluoropolymer may be a substance that has flexibility and flame retardancy by itself.
[0065] The polyurethane polymer is not particularly limited as long as it is a normal polyurethane produced by polymerization of a polyol and a polyisocyanate. Here, the polyol may be, for example, a normal polyol used in the production of polyurethane, and may be one or more selected from the group consisting of polyether polyol, polyester polyol, polyamide polyol, polyesteramide polyol, polythioether polyol, polycarbonate polyol, polyacetal polyol, polyolefin polyol, polysiloxane polyol, acrylic polyol, and silicone polyol. The polyisocyanate may include, for example, a typical polyisocyanate used in the production of polyurethane, and may be one or more selected from the group consisting of toluene diisocyanate, isophorone diisocyanate, cyclohexane-1,4-diisocyanate, 4,4-dicyclohexylmethane diisocyanate, 4,4-di(aminocyclohexyl)methane hexamethylene diisocyanate, 1,4-phenylene diisocyanate, 4,4-diphenylmethane diisocyanate, xylene diisocyanate, 1,5-naphthalene diisocyanate, trimethylhexamethylene diisocyanate, and norborane diisocyanate.
[0066] The polyolefin polymer may be, for example, one or more selected from the group consisting of polyethylene, polypropylene, polybutylene, polypentene, polyvinylidene fluoride, and polymethyl methacrylate.
[0067] The silicon-based polymer may be, for example, one or more selected from the group consisting of silicon elastomer, polydimethylsiloxane, polymethylethylsiloxane, polydiethylsiloxane, polymethylphenylsiloxane, polydiphenylsiloxane, and polyethylphenylsiloxane.
[0068] The content of the flexible polymer may be 75% by weight to 99% by weight, 90% by weight to 97% by weight, or 94% by weight to 97% by weight based on the total amount of the coating layer. By forming a coating layer containing a flame retardant within the above range on the surface of an aerogel layer having excellent thermal insulation properties, the insulating sheet for a battery can have fire resistance and flame resistance or non-combustibility in addition to thermal insulation properties.
[0069] The coating layer may further include a flame retardant. The type of the flame retardant is not particularly limited, and may be, for example, at least one selected from the group consisting of inorganic flame retardants, phosphorus-based flame retardants, nitrogen compound-based flame retardants, silicon-based flame retardants, melamine-based flame retardants, halogen-based flame retardants, and polyhydric alcohol-based flame retardants.
[0070] The inorganic flame retardant may be at least one selected from the group consisting of metal oxides and metal hydroxides. For example, the inorganic flame retardant may be at least one selected from the group consisting of silicon oxide, magnesium hydroxide, aluminum hydroxide, antimony oxide, sodium carbonate, zinc oxide, iron oxide, tin oxide, zinc borate, and calcium borate, but is not limited thereto.
[0071] The phosphorus-based flame retardant includes a typical phosphorus-containing flame retardant, for example, one or more selected from the group consisting of phosphate, phosphonate, phosphinate, phosphine oxide, phosphazene, and ammonium salts thereof, but is not limited thereto.
[0072] The phosphorus-based flame retardant may have two or more hydroxyl groups at the functional group terminal. As a specific example, the phosphorus-based flame retardant may include ammonium phosphate having a multifunctional hydroxyl group. When a phosphorus-based flame retardant having a multifunctional hydroxyl group is used, excellent flame retardancy can be obtained.
[0073] The nitrogen compound-based flame retardant may be at least one selected from the group consisting of an aliphatic amine compound, an aromatic amine compound, a nitrogen-containing heterocyclic compound, a cyanide compound, an ammonium hydroxide, an aliphatic amide, an aromatic amide, urea, and thiourea, but is not limited thereto.
[0074] The silicone-based flame retardant may be one or more selected from the group consisting of silicone resins and silicone oils. The silicone resin may include a resin having a structure of RSiO. Here, R represents an alkyl group having 1 to 10 carbon atoms, such as a methyl group, an ethyl group, or a propyl group, an aromatic group, or a substituent in which one or more of the hydrogens of the alkyl group and the aromatic group are substituted with a vinyl group. The silicone oil may be one or more selected from the group consisting of polydimethylsiloxane and modified polydimethylsiloxane in which at least one methyl group on the side chain or end of polydimethylsiloxane is modified with one or more of hydrogen, an alkyl group, a cyclohexyl group, a phenyl group, a benzyl group, an epoxy group, a polyether group, a carboxyl group, a mercapto group, a chloroalkyl group, an alkyl alcohol ester group, an alcohol group, an allyl group, a vinyl group, and a trifluoromethyl group, but is not limited thereto.
[0075] The melamine-based flame retardant may be at least one selected from the group consisting of melamine phosphate, dimelamine phosphate, melamine pyrophosphate, and melamine cyanurate, but is not limited thereto.
[0076] The halogen-based flame retardant can be any halogen-based compound that can act as a flame retardant, without limitation. For example, the halogen-based flame retardant can be one or more selected from the group consisting of decabromodiphenyl ether, decabromodiphenylethane, tetrabromobisphenol-A, tetrabromobisphenol-A epoxy oligomer, octa-bromotrimethylphenylindane, ethylene-bis-tetrabromophthalimide, tris(tribromophenol)triazine, and brominated polystyrene, but is not limited thereto.
[0077] The polyhydric alcohol flame retardant may be, for example, one or more selected from the group consisting of pentaerythritol, dipentaerythritol, trimethylolpropane, and ethylene glycol. As a specific example, the polyhydric alcohol flame retardant may be dipentaerythritol.
[0078] The flame retardant may be a phosphorus-based flame retardant or a polyhydric alcohol-based flame retardant, in which case flame retardancy can be ensured without emitting harmful substances.
[0079] The flame retardant may contain a phosphorus-based flame retardant and a polyhydric alcohol-based flame retardant in a weight ratio of 1:0.1 to 1:0.5, 1:0.1 to 1:0.4, 1:0.15 to 1:0.35, or 1:0.15 to 0.25. When the phosphorus-based flame retardant and the polyhydric alcohol-based flame retardant are used in combination within the above range, the elastic modulus of the coating layer is excellent, and the flame retardancy of the heat insulating sheet can be improved.
[0080] The content of the flame retardant may be 1 wt% to 25 wt%, 3 wt% to 10 wt%, or 3 wt% to 6 wt% based on the total amount of the coating layer. By forming a coating layer containing a flame retardant within the above range on the surface of an aerogel layer with excellent thermal insulation, the insulating sheet for a battery can have fire resistance and flame resistance or non-combustibility in addition to thermal insulation.
[0081] The coating layer may not include a filler, and the filler may be, for example, at least one selected from the group consisting of fumed silica, diatomaceous earth, halloysite, carbon nanotubes, perlite, silica, alumina, barium sulfate, clay, talc, mica powder, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum borate, barium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, barium zirconate, calcium zirconate, and vermiculite, but is not limited thereto.
[0082] The aerogel layer may be a hexahedron having an upper surface, a lower surface, and a side surface of an edge region between the upper surface and the lower surface, and a coating layer may be formed so as to cover the entire surface of the aerogel layer.
[0083] As a specific example, the coating layer may cover the entire surface of the aerogel layer, including the upper, lower and side surfaces. The battery insulation sheet having the coating layer formed so as to cover the entire surface of the aerogel layer may be disposed between the cells, and the upper and lower surfaces of the battery insulation sheet may face the cells disposed on both sides of the battery insulation sheet. In addition, since the flame-retardant coating layer is formed on the entire surface of the battery insulation sheet, the insulation sheet is prevented from burning alone, and when one cell is overheated, the flame is first blocked to suppress the spread of the flame to the adjacent cells, and the flame is effectively prevented from spreading inside the battery module having the plurality of cells.
[0084] The thickness of the coating layer may be 20% or less, 1% to 20%, 5% to 17%, or 8% to 12% of the total thickness of the battery insulation sheet. By forming the coating layer with a thickness within the above range, the sheet can have excellent heat insulation properties as well as flame retardancy or non-combustibility.
[0085] The coating layer includes the flexible polymer and a flame retardant dispersed in the flexible polymer, the flexible polymer being at least one selected from the group consisting of polyurethane-based polymers and silicon-based polymers, and the flame retardant being at least one selected from the group consisting of polyhydric alcohol-based flame retardants and phosphorus-based flame retardants. In this case, the aerogel layer can be prevented from falling off or scattering due to an external impact, improving workability and preventing contamination of the mechanism, and the coating layer can have excellent heat insulation and flame retardancy or non-combustibility.
[0086] In one embodiment, the coating layer may have an elastic modulus of 8 MPa or less as measured by ASTM D882. Specifically, the coating layer may have an elastic modulus of 1 MPa to 8 MPa, 3 MPa to 7 MPa, or 3 MPa to 5 MPa as measured by ASTM D882.
[0087] According to one embodiment, a method for manufacturing an insulation sheet for a battery includes forming an aerogel layer including an aerogel, and forming a coating layer to cover an entire surface of the aerogel layer. The coating layer may include a flexible polymer and a flame retardant dispersed in the flexible polymer, and the coating layer may have an elastic modulus of 8 MPa or less as measured by ASTM D882.
[0088] In one embodiment, forming the aerogel layer may include mixing a functional material, including a binder, a dispersant, or a combination thereof, with a solvent to produce a solvent mixture, mixing the solvent mixture and an aerogel to produce an aerogel mixture, and mixing the aerogel mixture and a fibrous support to produce an aerogel composition.
[0089] In the step of preparing the solvent mixture by mixing the functional material with the solvent, a binder may be mixed with the solvent, or a binder and a dispersant may be mixed with the solvent.
[0090] The solvent may be one or more selected from the group consisting of polar solvents and non-polar solvents.
[0091] The polar solvent may be one or more selected from the group consisting of water and alcohol-based solvents.
[0092] The water may be, for example, one or more types selected from the group consisting of purified water and ultrapure water.
[0093] The alcohol-based solvent may be, for example, one or more selected from the group consisting of methanol, ethanol, propanol, pentanol, butanol, hexanol, ethylene glycol, propylene glycol, diethylene glycol, and glycerol, but is not limited thereto.
[0094] The non-polar solvent may include a hydrocarbon solvent, for example, one or more selected from the group consisting of hexane, pentane, heptane, toluene, and benzene, and more preferably, an alkane solvent such as hexane, or a mixture containing an alkane solvent, but is not limited thereto.
[0095] The solvent may include water. When water is used as the solvent, raw material costs and post-treatment costs can be effectively reduced. However, when water is used as the solvent, there is a problem that it is difficult to mix with the hydrophobic aerogel. In one embodiment, the aerogel is uniformly dispersed by controlling the mixing step design, mixing conditions, addition and amount of binder and dispersant, etc. When the aerogel is uniformly dispersed in the composition in this way, it is possible to form an insulating sheet for a battery with excellent insulation properties, durability, and low dust properties at a thin thickness without using a large amount of binder.
[0096] The solvent may be contained in such a way that the weight ratio of the solvent to the total amount of solids in the aerogel composition is 1:1 to 1:90. For example, the weight ratio of the solvent to the total amount of solids in the aerogel composition may be 1:50 to 1:70, 1:20 to 1:30, or 1:2 to 1:10. By controlling the weight ratio of the solvent to the total amount of solids within the above range, it is possible to achieve both dispersibility, coatability, and phase stability.
[0097] The specific explanation regarding the binder and dispersant may be as described above.
[0098] In the step of preparing the aerogel mixture by mixing the solvent mixture and the aerogel, the specific description of the aerogel may be the same as that described above.
[0099] In the step of preparing an aerogel composition by mixing the aerogel mixture and the fibrous support, the specific description of the fibrous support may be as described above.
[0100] In each of the steps of preparing a solvent mixture by mixing a functional material including a binder, a dispersant, or a combination thereof with the solvent, preparing an aerogel mixture by mixing the solvent mixture and an aerogel, and preparing an aerogel composition by mixing the aerogel mixture and a fibrous support, a mixer may be used during mixing. For example, the mixer may include, but is not limited to, a planetary mixer, a PD mixer, a thinky mixer, a C-mixer, etc.
[0101] As a specific example, a planetary mixer may be used to mix the solvent mixture and the aerogel. When the solvent mixture and the aerogel are mixed using the planetary mixer, the aerogel can be uniformly dispersed in the solvent.
[0102] The planetary mixer may be a device that can be used to mix or stir different materials to produce a homogenous mixture, and may include blades that are capable of planetary motion.
[0103] In one embodiment, the planetary mixer may include one or more planetary blades and one or more high-speed dispersion blades. As a specific example, the planetary mixer may include one or more planetary blades and one or more high-speed dispersion blades.
[0104] The planetary blades and high speed dispersion blades rotate continuously about their axes, and the rotational speed may be expressed in units of rotations per minute (rpm).
[0105] In one embodiment, the planetary mixer may include a first blade and a second blade having different rotation axes. For example, the first blade may be a low-speed blade, and the second blade may be a high-speed blade. Here, low speed and high speed refer to the relative rotation speeds of the first blade and the second blade. As a specific example, the first blade may be an open blade, and the second blade may be a Despa blade.
[0106] The rotation speed of the first blade may be, for example, 10 rpm to 100 rpm, 10 rpm to 60, or 30 rpm to 70 rpm, and the rotation speed of the second blade may be, for example, 100 rpm to 2000 rpm, 100 rpm to 1000 rpm, 300 rpm to 1700 rpm, or 500 rpm to 1700 rpm.
[0107] When the functional material is mixed in the solvent, the rotation speed of the first blade may be 10 rpm to 60 rpm, 20 rpm to 50 rpm, or 30 rpm to 40 rpm, and the rotation speed of the second blade may be 300 rpm to 1700 rpm, 600 rpm to 1000 rpm, or 700 rpm to 800 rpm. By mixing the solvent and the functional material as described above, a solvent mixture in which the binder, dispersant, or a combination thereof is uniformly dispersed is prepared, and aerogel mixing in the subsequent step can be performed more easily.
[0108] When the solvent mixture and the aerogel powder are mixed, the rotation speed of the first blade of the mixer may be 30 rpm to 70 rpm, 40 rpm to 70 rpm, or 60 rpm to 70 rpm, and the rotation speed of the second blade may be 500 rpm to 1700 rpm, 600 rpm to 1600 rpm, or 800 rpm to 1500 rpm. By adding the aerogel powder to the solvent mixture and mixing it as described above, it is possible to prevent the aerogel powder from agglomerating with each other and induce uniform dispersion.
[0109] When the aerogel mixture and the fibrous support are mixed, the rotation speed of the first blade of the mixer may be 10 rpm to 60 rpm, 20 rpm to 50 rpm, or 30 rpm to 40 rpm, and the rotation speed of the second blade may be 300 rpm to 1700 rpm, 400 rpm to 1500 rpm, or 800 rpm to 1200 rpm. When the aerogel mixture and the fibrous support are mixed in this way, the air bubbles in the composition are removed, the viscosity is adjusted, and the fibrous support is easily dispersed between the uniformly dispersed aerogel, so that the aerogel may be present in the composition in a form in which the periphery of the fibrous support is covered by the aerogel. Here, a binder is present between the aerogel and the fibrous support, which can improve the binding force between the aerogel and the fibrous support.
[0110] In one embodiment, the aerogel layer may be formed in a single layer structure or a multi-layer structure. When the aerogel layer is formed in a multi-layer structure, the aerogel layer may be formed in 2 to 10 layers, 2 to 7 layers, or 2 to 5 layers.
[0111] The aerogel layer can be formed by conventional methods such as extrusion, coating, casting, etc. of the aerogel composition.
[0112] By forming an aerogel layer by the method according to an embodiment, the durability of the battery insulation sheet is improved in addition to the thermal insulation property, and the aerogel can be prevented from falling off and generating dust when the battery insulation sheet is manufactured or installed inside an apparatus.
[0113] In one embodiment, the step of forming a coating layer to cover at least two surfaces of the entire surface of the aerogel layer may be performed by dipping the aerogel layer into a coating layer forming liquid.
[0114] The coating layer forming liquid may include a flexible polymer, or a flexible polymer and a flame retardant, the specific details of which may be the same as those described above.
[0115] When the aerogel layer is dipped into the coating layer forming liquid, the coating layer forming liquid may be dispersed or dissolved in a suitable solvent. In this case, the viscosity of the coating layer may be controlled to form a uniform coating layer.
[0116] In one embodiment, the aerogel layer may be dipped into a coating layer forming solution and then dried at a temperature equal to or higher than the boiling point of the solvent to produce an insulating sheet for a battery according to one embodiment.
[0117] In one embodiment, the method may further include a step of crosslinking the aerogel layer after dipping the aerogel layer in the coating layer forming liquid, which may improve the cohesive strength between the aerogel layer and the coating layer.
[0118] The crosslinking method is not particularly limited, and may be, for example, thermal crosslinking, ultraviolet (UV) crosslinking, or the like.
[0119] The thermal crosslinking may be carried out at a temperature of 25° C. to 150° C., and the reaction time may be 10 seconds to 30 minutes.
[0120] The ultraviolet crosslinking may be carried out by irradiating with UV light for 10 seconds to 5 minutes.
[0121] In the case of the UV crosslinking, the coating layer forming solution may further include a crosslinking agent.
[0122] The crosslinking agent is not particularly limited, and may be, for example, one or more compounds selected from the group consisting of polyfunctional acrylate compounds, isocyanate compounds, epoxy compounds, aziridine compounds, and metal chelate compounds.
[0123] The polyfunctional acrylate compound may be, for example, one or more compounds selected from the group consisting of pentaerythritol tri / tetraacrylate, dipentaerythritol hexaacrylate, trimethylolpropane triacrylate, ethylene glycol diacrylate, and hexamethylene diacrylate.
[0124] The isocyanate compound may be, for example, one or more compounds selected from the group consisting of toluene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, isoform diisocyanate, tetramethylxylene diisocyanate, and naphthalene diisocyanate.
[0125] The epoxy compound may be, for example, one or more selected from the group consisting of ethylene glycol diglycidyl ether, triglycidyl ether, trimethylolpropane triglycidyl ether, N,N,N',N'-tetraglycidylethylenediamine, and glycerin diglycidyl ether.
[0126] The aziridine compound may be, for example, one or more selected from the group consisting of N,N'-toluene-2,4-bis(1-aziridinecarboxylate), N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxylate), triethylenemelamine, bisisopropyl-1-(2-methylaziridine), and tri-1-aziridinylphosphine oxide.
[0127] The metal chelate compound may include, for example, a compound in which a polyvalent metal such as aluminum, iron, zinc, tin, titanium, antimony, magnesium, or vanadium is coordinated to acetylacetone or ethyl acetoacetate.
[0128] When the ultraviolet (UV) crosslinking is performed, a photoinitiator may be further included.
[0129] The photoinitiator is not particularly limited, and may be, for example, one or more selected from the group consisting of benzophenone, acetophenone, chloroacetophenone, diethoxyacetophenone, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, benzoin benzoic acid, benzoin methyl benzoate, benzoin dimethyl ketal, 2,4-diethylthioxanthone, benzyl diphenyl sulfide, tetramethylthiuram monosulfide, azobisisobutyronitrile, benzyl, dibenzyl, diacetyl, beta chloroanthraquinone, thioxanthone, and 2-ethylanthraquinone.
[0130] In one embodiment, the insulating sheet for a battery may have a substrate disposed on one or both sides, where one side refers to the upper or lower side of the insulating sheet for a battery on which a coating layer is formed, and both sides refer to the upper and lower sides of the insulating sheet for a battery.
[0131] The substrate may be of any type, including, for example, a resin, a metal, an inorganic material other than a metal, or a composite thereof. The substrate may be in any form, including, for example, a film, a thin film, a sheet, or the like.
[0132] The resin may include, for example, one or more selected from the group consisting of polyethylene, polypropylene, polystyrene, polyethylene terephthalate, and polyamide.
[0133] The metal may include at least one selected from the group consisting of copper, nickel, cobalt, iron, chromium, vanadium, palladium, ruthenium, rhodium, molybdenum, tungsten, iridium, silver, gold, and platinum. When using a substrate made of the above metal material, the substrate may be subjected to anti-corrosion treatment, insulation treatment, etc., as necessary.
[0134] The inorganic material may include one or more selected from the group consisting of calcium carbonate (CaCO3), talc, and mica.
[0135] As a specific example, the substrate may include an inorganic material, and more specifically, may include mica, which can improve the heat insulating property and durability of the heat insulating sheet.
[0136] A battery module according to an embodiment may include a plurality of cells, and the battery insulating sheets disposed between the plurality of cells, respectively.
[0137] The cell may be a secondary battery cell. The secondary battery may be, for example, a lithium secondary battery. The lithium secondary battery may be manufactured in various forms, such as a lithium ion battery, an all-solid-state battery, or a lithium metal battery. For example, the lithium secondary battery may have a structure in which a positive electrode plate and a negative electrode plate, on which a positive electrode active material and a negative electrode active material are respectively applied, are arranged with a separator sandwiched therebetween, and are sealed in a battery case together with an electrolyte to form a secondary battery cell. Depending on the shape of the battery case to be formed, it may be classified into a cylindrical type, a square type, or a pouch type, and a plurality of secondary battery cells are connected in series or parallel to form a battery module.
[0138] Such secondary batteries require high stability. For example, if the secondary batteries are overcharged, decomposition reactions of the positive electrode active material or electrolyte and other side reactions may occur, and these reactions may release heat, which may eventually lead to an explosion of the secondary battery cell.
[0139] In this regard, in the present invention, by disposing an insulating sheet between each of the cells, which includes a coating layer formed so as to cover part or all of the surface, the insulating sheet has excellent insulation properties as well as fire resistance and flame retardancy or non-combustibility, and can suppress the spread of heat and flame to adjacent cells due to thermal runaway of a cell.
[0140] FIG. 1 is a schematic diagram showing a plurality of cells and a battery insulating sheet disposed between each of the cells.
[0141] 1, the insulating sheet 100 for a battery according to an embodiment may be disposed between the cells 200 in a battery module including the cells 200. By forming the insulating sheet 100 for a battery according to an embodiment between the cells 200, a flame is first blocked when the battery is overheated, and the spread of the flame to other cells is minimized, thereby providing a battery module with improved safety, and further providing a battery pack including the battery module.
[0142] FIG. 2 is a schematic diagram showing the structure of a battery insulating sheet according to one embodiment.
[0143] Referring to FIG. 2, the insulation sheet for a battery 100 may be formed in a structure including an aerogel layer 110 and a coating layer 120 formed on the entire surface including the upper surface, the lower surface, and the edge side between the upper surface and the lower surface of the aerogel layer.
[0144] Specific examples of the present invention will be presented below. However, the examples described below are merely for the purpose of specifically illustrating or explaining the present invention, and the present invention should not be limited thereto. Furthermore, since the contents not described here can be sufficiently inferred by a person skilled in the art, the description thereof will be omitted.
[0145] (Manufacture of heat insulating sheets for batteries) Example 1 1. Aerogel Layer Fabrication Polyvinyl alcohol (Sigma Aldrich, Poly(vinyl alcohol)) was added as a binder to ultrapure water as a solvent, and then mixed under conditions of an open blade of 30 rpm and a despa blade of 700 rpm to produce a solvent mixture. 2Aerogel mixture was prepared by adding aerogel having a particle size of 1 / g and mixing with an open blade at 70 rpm and a Despa blade at 1500 rpm. Glass wool was added to the aerogel mixture and mixing with an open blade at 30 rpm and a Despa blade at 1200 rpm to prepare an aerogel composition. A planetary mixer (DIENTEK, PT-005) was used for mixing.
[0146] The solid content of the prepared aerogel composition was confirmed to be 50 wt % aerogel, 40 wt % glass wool, and 10 wt % polyvinyl alcohol.
[0147] The prepared aerogel composition was used to form an aerogel layer.
[0148] 2. Manufacture of insulation sheets for batteries The aerogel layer thus prepared was dipped into a coating layer forming solution to form a coating layer on the entire surface of the aerogel layer. Here, the coating layer forming solution was prepared with a composition of 94.8 wt% polyurethane (Shenzhen Jiian Chemical, PU solution), 4 wt% ammonium phosphate (Merck, Ammonium Phosphate) and 1.2 wt% dipentaerythritol (Merck, Dipentaerythritol) as flame retardants.
[0149] The aerogel layer was dipped in the coating layer forming liquid and then dried to produce an insulating sheet for a battery having a coating layer formed on the entire surface of the aerogel layer. It was confirmed that the total thickness of the insulating sheet for a battery produced was 3 mm, the thickness of the aerogel layer was 2.7 mm, and the thickness of the coating layer was 0.15 mm on each of the upper and lower surfaces and edges of the aerogel layer.
[0150] Example 2 The coating layer was prepared in the same manner as in Example 1, except that a coating layer forming solution having a composition of 94.8 wt % of silicone elastomer (Gelest, EXsil 100) and 4 wt % of ammonium phosphate (Merck, Ammonium Phosphate) and 1.2 wt % of dipentaerythritol (Merck, Dipentaerythritol) as flame retardants was used.
[0151] Example 3 The insulation sheet was manufactured in the same manner as in Example 1, except that the thicknesses of the aerogel layer and the coating layer were adjusted in Example 1. Specifically, it was confirmed that the total thickness of the insulation sheet for a battery was 3 mm, the thickness of the aerogel layer was 2.6 mm, and the thickness of the coating layer was 0.2 mm.
[0152] Example 4 The insulation sheet was manufactured in the same manner as in Example 1, except that the thicknesses of the aerogel layer and the coating layer were adjusted in Example 1. Specifically, it was confirmed that the total thickness of the insulation sheet for a battery was 3 mm, the thickness of the aerogel layer was 2.4 mm, and the thickness of the coating layer was 0.3 mm.
[0153] Example 5 The same method as in Example 1 was used to prepare the coating layer, except that a coating layer forming solution having a composition of 80 wt% polyurethane (PU solution, Shenzhen Jiian Chemical), 15 wt% ammonium phosphate (Ammonium Phosphate, Merck) and 5 wt% dipentaerythritol (Dipentaerythritol, Merck) as flame retardants was used.
[0154] Example 6 The same method as in Example 1 was used to prepare the coating layer, except that a coating layer forming solution having a composition of 97.6 wt% polyurethane (PU solution, Shenzhen Jiian Chemical), 1.8 wt% ammonium phosphate (Ammonium Phosphate, Merck) and 0.6 wt% dipentaerythritol (Dipentaerythritol, Merck) as flame retardants was used.
[0155] Example 7 The same method as in Example 1 was used to prepare the coating layer, except that a coating layer forming solution having a composition of 94.8 wt% polyurethane (PU solution, Shenzhen Jiian Chemical), 4.0 wt% ammonium dihydrogen phosphate as a flame retardant, and 1.2 wt% dipentaerythritol (Merck) was used.
[0156] Example 8 The same method as in Example 1 was used to prepare the coating layer, except that a coating layer forming solution having a composition of 95 wt% polyurethane (Shenzhen Jiian Chemical, PU solution) and 5 wt% ammonium hydroxide (Merck, Aluminum hydroxide) as a flame retardant was used.
[0157] Comparative Example 1 The aerogel layer was produced in the same manner as in Example 1, except that an aerogel layer without a coating layer formed on the surface was used. It was confirmed that the aerogel layer in the produced insulating sheet for a battery had a total thickness of 3 mm.
[0158] Comparative Example 2 The coating layer was prepared in the same manner as in Example 1, except that a coating layer-forming solution having a composition of 100 wt % polyurethane (PU solution, Shenzhen Jiian Chemical) was used.
[0159] Comparative Example 3 The coating layer was prepared in the same manner as in Example 1, except that a coating layer forming solution having a composition of 84.8 wt% polyurethane (PU solution, Shenzhen Jiian Chemical), 4 wt% ammonium phosphate (Ammonium Phosphate, Merck) and 1.2 wt% dipentaerythritol (Dipentaerythritol, Merck) as flame retardants, and 10 wt% fumed silica as a filler was used.
[0160] Comparative Example 4 The method of manufacture was the same as that of Example 1, except that the coating layer was formed only on the upper surface of the aerogel layer, and the aerogel layer was formed to a thickness of 2.7 mm and the coating layer was formed to a thickness of 0.3 mm.
[0161] FIG. 3 is a schematic diagram showing the structure of the insulating sheet for a battery according to Comparative Example 4. As shown in FIG.
[0162] Referring to FIG. 3, the insulation sheet for a battery 100 is formed to have a structure including an aerogel layer 110 and a coating layer 120 formed on the upper surface of the aerogel layer.
[0163] Comparative Example 5 The same method as in Example 1 was used to manufacture the aerogel layer, except that the coating layer was formed only on the edge side between the upper and lower surfaces of the aerogel layer, and the aerogel layer was formed to a thickness of 3 mm.
[0164] FIG. 4 is a schematic diagram showing the structure of a heat insulating sheet for a battery according to Comparative Example 5. As shown in FIG.
[0165] Referring to FIG. 4, the insulation sheet for a battery 100 is formed to have a structure including an aerogel layer 110 and a coating layer 120 formed on the edge side between the upper and lower surfaces of the aerogel layer.
[0166] (Experimental Example) Experimental example 1: Evaluation of coating layer properties The elastic modulus of the coating layer of the insulating sheets for batteries prepared in Examples 1 to 8 and Comparative Examples 1 to 5 was evaluated.
[0167] Specifically, the elastic modulus was measured according to ASTM D882, and the measurement results are shown in Tables 1 and 2 below.
[0168] Experimental example 2: Evaluation of the physical properties of insulating sheets for batteries 1.Insulation evaluation The heat insulating properties were evaluated using the heat insulating sheets produced in Examples 1 to 8 and Comparative Examples 1 to 5.
[0169] Specifically, each heat insulating sheet was placed between a pair of opposing 1T thick aluminum plates, which were then placed on a heat press, and the upper plate of the heat press was heated to 350° C., while the lower plate of the heat press was not heated and was kept at the starting temperature of 40° C. A pressure of 20 kN was then applied to the lower plate of the heat press, and the maximum temperature of the lower plate of the heat press after 11 minutes was measured, and the results are shown in Tables 1 and 2 below.
[0170] 2.Compressibility evaluation The heat insulating sheets produced in Examples 1 to 8 and Comparative Examples 1 to 5 were produced to a size of 140 mm×100 mm, and used to evaluate compression performance.
[0171] Specifically, the thickness ratio when a load of 5kN was applied was measured based on the thickness when a load of 40kN was applied using UTM equipment, and is shown in Tables 1 and 2 below.
[0172] 3. Flame retardancy evaluation The heat insulating sheets produced in Examples 1 to 8 and Comparative Examples 1 to 5 were used to evaluate flame retardancy.
[0173] Specifically, the flame retardancy was evaluated according to the UL-94V flame retardancy rating test method (UL94V Test (Vertical Burning Test)) into the grades V-0, V-1, and V-2, and the results are shown in Tables 1 and 2 below.
[0174] 4. Dustiness evaluation The heat insulating sheets manufactured in Examples 1 to 8 and Comparative Examples 1 to 5 were used to evaluate dust characteristics.
[0175] The dust characteristics were evaluated by a method of measuring weight loss by vibration evaluation. Specifically, a test piece of 140 mm x 100 mm was subjected to vibration of 30 Hz for 1 hour using vibration evaluation equipment, and the weight loss was measured, and the results are shown in Tables 1 and 2 below. If the weight loss was less than 1%, it was evaluated as good, and if it was 1% or more, it was evaluated as bad.
[0176] [Table 1]
[0177] [Table 2]
[0178] In Table 2 above, NG means that the evaluation results are below V-2 rating.
[0179] Referring to Tables 1 and 2 above, it can be seen that, in Comparative Example 1, the aerogel layer is provided at a thickness of 3 mm compared to Examples 1 to 8, and thus the heat insulation is high, but the compression performance and dust resistance are reduced due to the absence of a coating layer. In Comparative Example 2, the coating layer does not contain a flame retardant, and thus the flame retardancy cannot be ensured. In Comparative Example 3, the coating layer contains 10 wt % of filler, and thus the elastic modulus of the coating layer and the compressibility of the heat insulating sheet are significantly reduced. In Comparative Example 4, the coating layer is formed only on the upper and lower surfaces of the aerogel layer, and thus the dust resistance is reduced, and in Comparative Example 5, the coating layer is formed only on the edge side of the aerogel layer, and thus the compressibility is reduced.
[0180] Therefore, it was confirmed that the use of the insulating sheet for a battery according to one embodiment of the present invention provides excellent insulation properties, compressibility, flame retardancy, and dust resistance.
[0181] Although the preferred embodiments of the present invention have been described above, the present invention is not limited thereto, and various modifications can be made within the scope of the claims, the detailed description of the invention, and the accompanying drawings, and it is to be understood that these modifications also fall within the scope of the present invention. [Explanation of symbols]
[0182] 100 Battery insulation sheet 110 Aerogel layer 120 Coating Layer 200 cells
Claims
1. an aerogel layer including an aerogel; a coating layer covering the entire surface of the aerogel layer; The coating layer includes a flexible polymer and a flame retardant dispersed in the flexible polymer, The coating layer has an elastic modulus of 8 MPa or less as measured by ASTM D882.
2. The aerogel has a BET specific surface area of 500 m 2 / g to 1,000m 2 The insulating sheet for a battery according to claim 1, wherein the elastic modulus is 1 / g.
3. The battery insulating sheet according to claim 1 , wherein the aerogel layer further comprises a fibrous support and a functional material comprising a binder, a dispersant, or a combination thereof.
4. The battery insulating sheet according to claim 3 , wherein the fibrous support comprises at least one selected from the group consisting of natural fibers, silica fibers, glass fibers, carbon fibers, graphite fibers, mineral fibers, and polymer fibers.
5. The battery insulating sheet according to claim 3 , wherein the binder is a water-based polymer binder.
6. The insulating sheet for a battery according to claim 3 , wherein the dispersing agent is at least one selected from the group consisting of a surfactant, a silane coupling agent, and a phosphate salt.
7. The aerogel layer contains, with respect to the total amount of the aerogel layer, 10% by weight to 90% by weight of the aerogel, 5% by weight to 70% by weight of the fibrous support, and 0.5% by weight to 20% by weight of the functional material. The insulating sheet for a battery according to claim 3.
8. The battery insulating sheet according to claim 1 , wherein the flexible polymer is at least one selected from the group consisting of a fluorine-based polymer, a polyurethane-based polymer, a polyolefin-based polymer, and a silicon-based polymer.
9. 2. The battery insulating sheet according to claim 1, wherein the flame retardant is at least one selected from the group consisting of inorganic flame retardants, phosphorus-based flame retardants, nitrogen compound-based flame retardants, silicon-based flame retardants, melamine-based flame retardants, halogen-based flame retardants, and polyhydric alcohol-based flame retardants.
10. The battery insulating sheet according to claim 1 , wherein the flame retardant comprises a phosphorus-based flame retardant and a polyhydric alcohol-based flame retardant.
11. The battery insulating sheet according to claim 10, wherein the flame retardant comprises a phosphorus-based flame retardant and a polyhydric alcohol-based flame retardant in a weight ratio of 1:0.1 to 1:0.
5.
12. The battery insulating sheet according to claim 1 , wherein the content of the flame retardant is 1% by weight to 25% by weight based on the total weight of the coating layer.
13. The insulating sheet for a battery according to claim 1 , wherein the coating layer does not contain a filler.
14. The battery insulating sheet according to claim 1 , wherein the coating layer has a thickness of 20% or less of a total thickness of the battery insulating sheet.
15. The flexible polymer is at least one selected from the group consisting of polyurethane-based polymers and silicone-based polymers, The battery insulating sheet according to claim 1 , wherein the flame retardant is at least one selected from the group consisting of polyhydric alcohol-based flame retardants and phosphorus-based flame retardants.
16. forming an aerogel layer comprising aerogel; forming a coating layer to cover the entire surface of the aerogel layer; The coating layer includes a flexible polymer and a flame retardant dispersed in the flexible polymer, The coating layer has an elastic modulus of 8 MPa or less as measured by ASTM D882.
17. A plurality of cells; and the insulating sheet according to any one of claims 1 to 15, disposed between each of the plurality of cells.
Citation Information
Patent Citations
Composite flame retardant for non-halogen-based resin
JP2000351906A
Flame-retardant polyvinyl alcohol-based fiber
JP2001316940A
Vacuum insulator, insulating box, and refrigerator
JP2016035320A
Outer packaging material for vacuum heat insulation material, vacuum heat insulation material, and article with vacuum heat insulation material
JP2021004647A
Insulating material for battery pack and battery pack
JP2021144879A